Differential Adaptive Response of Growing Bones From Two Female Inbred Mouse Strains to Voluntary Cage‐Wheel Running. (12th February 2018) - Schlecht, Stephen H.; Ramcharan, Melissa A.; Yang, Yueqin; Smith, Lauren M; Bigelow, Erin MR; Nolan, Bonnie T; Moss, Drew E; Devlin, Maureen J; Jepsen, Karl J
ABSTRACT: The phenotypic response of bones differing in morphological, compositional, and mechanical traits to an increase in loading during growth is not well understood. We tested whether bones of two inbred mouse strains that assemble differing sets of traits to achieve mechanical homeostasis at adulthood would show divergent responses to voluntary cage‐wheel running. Female A/J and C57BL6/J (B6) 4‐week‐old mice were provided unrestricted access to a standard cage‐wheel for 4 weeks. A/J mice have narrow and highly mineralized femora and B6 mice have wide and less mineralized femora. Both strains averaged 2 to 9.5 km of running per day, with the average‐distance run between strains not significantly different ( p  = 0.133). Exercised A/J femora showed an anabolic response to exercise with the diaphyses showing a 2.8% greater total area (Tt.Ar, p  = 0.06) and 4.7% greater cortical area (Ct.Ar, p  = 0.012) compared to controls. In contrast, exercised B6 femora showed a 6.2% ( p  < 0.001) decrease in Tt.Ar ( p  < 0.001) and a 6.7% decrease in Ct.Ar ( p  = 0.133) compared to controls, with the femora showing significant marrow infilling ( p  = 0.002). These divergent morphological responses to exercise, which did not depend on the daily distance run, translated to a 7.9% ( p  = 0.001) higher maximum load (ML) for exercised A/J femora but no change in ML for exercised B6 femora compared to controls. A consistent response was observed for the humeri but not the vertebral bodies. This differential outcome to exercise has not been previously observed in isolated loading or forced treadmill running regimes. Our findings suggest there are critical factors involved in the metabolic response to exercise during growth that require further consideration to understand how genotype, exercise, bone morphology, and whole‐bone strength interact during growth. © 2018 The Authors. JBMR Plus is published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.